Microstructures and properties of equimolar AlCoCrCuFeNi high-entropy alloy additively manufactured by selective laser melting. (May 2020) - Wang, Yin; Li, Ruidi; Niu, Pengda; Zhang, Zhijian; Yuan, Tiechui; Yuan, Jiwei; Li, Kun
Abstract: An equimolar hexahydroxy AlCoCrCuFeNi high-entropy alloy (HEA) was produced by selective laser melting (SLM) gas-atomized powders, with emphasis on investigating its microstructure and properties. SLM printed AlCoCrCuFeNi HEA shows high crack sensitivity with faced centered cubic (FCC) and body-centered cubic (BCC) phases. High-angle grain boundary, segregation of Cu element and the misfit between BCC and FCC phase account for the crack formation during SLM process. The content of FCC phase gradually increases from 30.55% to 40.20% as VED increases from 52.08 J/mm 3 to 83.3 J/mm 3 . The formation of BCC is restrained owing to rapid solidification. Moreover, unique fine columnar grains growing along the building direction are perpendicular to the boundary of molten pools and present (001), (111) and (101) grain orientation. Also, the fine grains and the high-density dislocation network induced by rapid cooling of the SLMed AlCoCrCuFeNi HEA are observed. The SLMed AlCoCrCuFeNi HEA possesses outstanding properties with a Vickers hardness of 710.4 Hv compared to its counterpart prepared by traditional methods of 500 Hv. Highlights: An equimolar hexahydroxy AlCoCrCuFeNiTi high-entropy alloy is fabricated using selective laser melting. SLM-built HEA shows hierarchically various microstructure and dislocation network. Three typical structures including FCC phase, B2 phase and FCC phase are observed. SLM-built HEA exhibits Superior microhardness value of 710.4HV. Defects such as pores and cracks are analyzed in the study.